2021
DOI: 10.1038/s41598-021-83794-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple endogenous seed-born bacteria recovered rice growth disruption caused by Burkholderia glumae

Abstract: Burkholderia glumae is a causal agent of bacterial grain and seedling rot in rice, and is a threat to stable global food supply. The virulence of B. glumae was suppressed when it was inoculated on budding seed rather than on non-budding seed. To clarify the phenomena, pathogen titer inside the rice plant was measured by serial dilution plating of lysates from budding rice seedlings. Surprisingly, morphologically different types of colonies were observed on the plates. These ‘contaminated’ rice seed-born bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…To explore seed-borne bacteria that have biocontrol activity, we conducted a toxoflavin tolerance test. As toxoflavin is known to have antibacterial activity [ 10 ], the bacterial biocontrol agents against B. glumae may need to exhibit tolerance to this toxin. We examined the 10 IRBB1- and TN1-derived isolates of Pantoea and Paenibacillus and found that the latter were highly tolerant to toxoflavin ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To explore seed-borne bacteria that have biocontrol activity, we conducted a toxoflavin tolerance test. As toxoflavin is known to have antibacterial activity [ 10 ], the bacterial biocontrol agents against B. glumae may need to exhibit tolerance to this toxin. We examined the 10 IRBB1- and TN1-derived isolates of Pantoea and Paenibacillus and found that the latter were highly tolerant to toxoflavin ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…2, Sumitomo Chemical, Tokyo, Japan) and were grown in a growth chamber at 28 °C with 100% humidity under a 16 h:8 h photoperiod. Disease severity was evaluated by measuring the shoot length of the inoculated plants, as previously described [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations